Pengembangan Media Pembelajaran Bahasa Inggris Kelas 10 untuk Meningkatan Writing Skills Siswa - Romi Siswanto (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
Language competence consists of four competences to master it. The four competences are speaking, listening, writing, and reading. Speaking can be done spontaneously, but writing must be planned and organized. The purpose of this study is to design an applicable android operation-based learning media to help pupils develop their English writing proficiency. This study uses the Research and Development approach which was acclimated in the development of the ADDIE model. The experimenter designed a education media called